Impact of Smoking on Periodontal Health: A Comparative Study Between Libyan & Egyptian adult population - Fattah Sanfaz , Abdel (Libyan Journal of Public Health Practices, 2025)
Periodontal disease remains a major public health concern worldwide, with tobacco use identified as one of the most significant modifiable risk factors. This study aims to assess and compare the periodontal health status and the impact of smoking among the adult populations in Alexandria (Egypt) and Benghazi (Libya). A cross-sectional study involving 2,920 adult participants in both cities. Periodontal status was assessed using the Community Periodontal Index (CPI) and Loss of Attachment (LOA) scores. Participants were categorized based on smoking status, smoking type, and duration of smoking. Statistical analyses were conducted using Chi-square tests with significance set at P < 0.05. Heavy smokers demonstrated a significantly higher prevalence of deep periodontal pockets compared to non-smokers in Alexandria and Benghazi, 69.4% and 56.5%, respectively (P < 0.0001). Cigarette smoking was associated with more severe periodontal conditions than shisha smoking, particularly in Benghazi (P= 0.007). Duration of smoking was strongly associated with periodontal deterioration, with deep pockets present in 87.1% of long-term smokers in Alexandria and 73.7% in Benghazi (P < 0.0001). Smoking, particularly cigarette use and prolonged exposure, was significantly associated with worsening periodontal health. These findings underscore the importance of incorporating smoking cessation efforts into dental care and public health strategies to mitigate periodontal disease progression